Ethnophysics Studies in Various Indonesian Cultures: A Systematic Literature Review - Festiyed Festiyed; Asrizal Asrizal; Fatni Mufit; Yul Ifda Tanjung; Revi Gina Gunawan; Ilwandri Ilwandri; Zulherman Zulherman (Yayasan Keluarga Guru Mandiri, 2024)
Research related to ethnoscience from culture, local wisdom, and local potential in Indonesia in the last seven years has developed, but there are still few studies conducted in Physics Education. This study aims to identify and review ethnophysics research from various cultures in Indonesia. A systematic literature review method was used with four stages: identification, selection, eligibility, and inclusion. Of the 695 journal articles screened through Mendeley and Google Scholar applications, 12 were selected as research samples because they met the research criteria. The literature review shows that the cultural aspects studied are still limited to traditional dances, games, and houses. The research is also limited to several regions such as Jayapura, Demak, East Java, West Java, Jambi, West Sumatra, Aceh, South Sulawesi, and South Central Timor in a regional or ethnic context. The physics materials studied include measurement, waves, sound, reflection and refraction of light, lunar and solar eclipses, the concept of energy and its transformation, heat, density, gravity, Newton's law, balance, work, force, motion, magnetic fields, and electric fields. Further research can be done through cultural studies, local wisdom, or local potential from unreached areas in Indonesia. The findings of this study indicate the need for a broader and deeper exploration of ethnoscience in physics education through culture, local wisdom, and other local potential in Indonesia as a learning resource for students in the classroom.